Educational Thought of Shaykh Abdullah Fahim: A Review in the Study of Hadis - Khairul Nizam Bin Zainal Badri (Tasfiyah: Jurnal Pemikiran Islam, 2021)
This article examines Sheikh Abdullah Fahim's thoughts in hadith study education in Malaysia. In the late 19th and early 20th centuries, hadith studies were considered foreign among Malays because they were associated with the youth movement. Returning Sheikh Abdullah Fahim from Mecca in 1916, he introduced formal hadith studies in the madrassa where he taught. Uniquely, Sheikh Abdullah Fahim has a background in traditional method education with authoritative teachers in Mecca which is often associated with the educational methodology of the old movement. Thus, this raises the question of what educational characteristics Sheikh Abdullah Fahim highlighted in the field of hadith that rarely gets the attention of elders in the field. There are three goals to be achieved in this study, discussing the influence that underlies the thoughts of Sheikh Abdullah Fahim in the field of hadith, knowing the approach used by Sheikh Abdullah Fahim in studying the science of hadith and Sheikh Abdullah Fahim's contribution in the field of hadith. This research uses qualitative methods and library approaches to gather information. The results of the study found that Sheikh Abdullah Fahim did a great job in introducing the Nizami curriculum in madrassa studies and succeeded in producing a competent next generation to connect the knowledge of hadith teaching to the community.